Empirical research on human resource management as a production of ideology - Werner Nienhueser (Management Revue, 2011)
The article argues that empirical research on Human Resource Management creates a one-sided, distorted image of the reality of work and thus generates ideology. Such an ideology legitimises HR practices and favours the interests of entrepreneurs and managers. This assertion is illustrated and discussed using the case of empirical research in HRM in German-speaking countries, although the ideology assertion should also be valid for Anglo-Saxon countries. It is shown that HRM research mainly follows employer objectives; it primarily analyses performance-related variables. The surveyed HR practices focus on 'High Performance Works Systems', while other HR practices are largely ignored. Mainly organisational elites (managers, experts and other highly qualified employees) are surveyed as personnel and provide information about the situation in companies. Empirical research paints a unitaristic picture; depicting the employer and the role of HR management positively. Deviations from an employee-friendly HR strategy are overlooked or seen as relatively rare anomalies.
Keywords: C80; D22; M12; 650; ideology; power empirical research; images of work